Tetanus immunity in nursing home residents of Bolu, Turkey - Tamer Ali; Ozkardes Fatma; Karabay Oguz; Karaarslan Kazım (BMC, 2005)
Abstract Background Tetanus is a serious but vaccine-preventable disease and fatality rate of the disease is high in the neonates and the elderly. The aim of this study was to detect the tetanus antibody prevalence in the over sixty-year age residents of the nursing homes in Bolu. Methods A voluntary-based study was done in the residents of two nursing homes in Bolu, Turkey. Blood samples were taken from 71 volunteers residing in there nursing homes. Tetanus IgG antibodies were measured by a commercial ELISA kit. Results Among overall subjects, only 11 (15.7 %) had the protective tetanus antibody titers at the time of the study. Totally, 10 subjects were examined in emergency rooms due to trauma or accidents within the last ten years and, four (40%) of them had protective antibody levels. Of the remaining 61 subjects only 7 (11%) had protective antibody levels (p < 0.05) [Relative Risk = 3.49, 95% Confidence Interval 1.24-9.77]. Conclusions Tetanus antibody level is below the protective level in the majority of the over-sixty-year-age subjects residing in the nursing homes. Each over sixty-year age person in our country should be vaccinated. Until this is accomplished, at least, nursing home residents should be vaccinated during registration.